Dermatitis among Workers and Its Relation with Personal Protective Equipment - Alayyannur, Putri Ayuni; Malik Al Hakim, Muhammad; Rejeki Eviyanti Puspita Sari, Rr. Sri (Universitas Airlangga, 2024)
Introduction: Every workplace must make an occupational health effort to avoid health problems. Many workers underestimate the risks of the job and, therefore, do not use safety equipment even when available. The most often reported case of occupational skin illnesses, contact dermatitis, accounts for more than 85% of all cases. This study was conducted to occupational dermatitis and its relationship to personal protective equipment (PPE) use. Methods: The literature search was carried out in April 2021. The research sources were taken from several databases with the keywords dermatitis, occupational health, and personal protective equipment. The Google Scholar database found 17,710 articles, ScienceDirect found 1,264 articles, ProQuest found 888 articles, and PubMed found 452 articles. Of the entire database, only 36 articles met the inclusion criteria. Results: This literature review shows that dermatitis is experienced by workers in various sectors including health workers, hairdressers, scavengers, farmers, fishermen, manufacturing industry workers, printing workers, and construction workers. The use of PPE can reduce the risk of dermatitis. However, in some conditions, the use of PPE has no effect or can even cause dermatitis due to irritation and allergies to the ingredients contained in the PPE. The limitation of this research is that the articles that are the source of this review are only from 2016–2021.Conclusion: Dermatitis still occurs in various occupational sectors. The risk of dermatitis can be decreased by using PPE; however, it can also cause the occurrence of dermatitis itself.